Health Insurance for ‘People with Citizenship Problems’ and Inpatient Service:a Case Study of Ranong Province - Suphanchaimat, Rapeepong; Wisaijohn, Thunthita; Kantamaturapoj, Kanang; Saneerattanaprayul, Parinda; Kasemsup, Vijj; Putthasri, Weerasak; Limwattananonta, Supon (Journal of Health Science of Thailand, 2017)
‘Health Insurance Policy for People with Citizenship Problems’ (HIS-PCP) has been implemented according to the Cabinet Resolution on 23rd March 2010, aiming to increase access to care and reduce financial barrier impeding health utilization among the target population. This study therefore sought to evaluate the policy impacts in terms of inpatient (IP) visits, disease severity, admission days, and out-of-pocket payment through a case study of Kraburi hospital and Ranong hospital in Ranong province. Secondary data during fiscal year 2009-2012 (12-folder hospital records) were employed and analyzed by econometric models, namely, (1) Difference-in-Difference model to assess changes in IP visits, disease severity, and admission days in both hospitals, and (2) Two-part model to assess changes in out-of-pocket payment only in Kraburi hospital where data were feasible for the analysis. The findings revealed that HIS-PCP rendered the escalation in IP visits by 0.14 and 0.02 visits/ person/year in Kraburi hospital and Ranong hospital respectively, with no statistical significance. In addition, the policy did not alter disease severity upon admission in both hospitals. Nevertheless, length of stay was significantly expanded by 1 day/visit in Ranong hospital, and out-of-pocket payment of an inpatient in Kraburi hospital significantly decreased by 552 Baht/visit. In summary, the policy did not have a significant impact on increasing access to care, in particular, at an early onset of a disease, though decreasing trend in out-of-pocket payment was obviously noticeable. Developing local mechanisms with regards to health promotion and prevention to raise awareness of the right to health care are nuts and bolts in having the policy implemented more effectively in sustainable manner.